Design and Construction of Poultry Feather Plucking Machine with a 2 kg Processing Capacity - Setiawan, Apri; Setiawan, Dibyo; Agung Pratama, Boby; Rudy Rafly; Harry Prayoga Setyawan (Jurnal Teknik Mesin Mechanical Xplore, 2024)
The poultry industry plays a crucial role in meeting the growing global demand for meat. However, the feather plucking process remains a significant challenge, particularly for small-scale poultry farmers who often rely on manual methods that are time-consuming, labor-intensive, and potentially unhygienic. This study aimed to design and construct an affordable and efficient poultry feather plucking machine with a 2 kg processing capacity. The machine was designed using 3D modeling software and constructed using plastic materials for the bucket and rotating disc, and steel for the electric motor mount. The use of plastic components aimed to reduce production costs while maintaining efficiency and minimizing the risk of damage to poultry skin during the plucking process. Functional tests were conducted to evaluate the machine's performance, revealing an average processing time of 28 s per bird, a 30% reduction compared to manual plucking. The machine's efficiency was also assessed, demonstrating a 30% improvement over manual methods. The total production cost of the machine was Rp. 450,000, which is more economical than previous studies. Although the developed machine showed promising results, further study is needed to explore additional parameters such as energy consumption, maintenance requirements, and long-term durability. The incorporation of machine learning algorithms for automated cycle time optimization based on different poultry sizes and feather densities could also be investigated in future studies. Overall, this study contributes to the development of affordable and efficient poultry feather plucking machines, which can benefit small-scale poultry farmers and improve the overall efficiency of the poultry industry.